Web bloopers 60 common web design mistakes, and how to avoid them - Johnson, Jeff. (Amsterdam ; Boston : Morgan Kaufmann, 2003)
The dot.com crash of 2000 was a wake-up call, and told us that the Web has far to go before achieving the acceptance predicted for it in '95. A large part of what is missing is quality; a primary component of the missing quality is usability. The Web is not nearly as easy to use as it needs to be for the average person to rely on it for everyday information, commerce, and entertainment. In response to strong feedback from readers of GUI BLOOPERS calling for a book devoted exclusively to Web design bloopers, Jeff Johnson calls attention to the most frequently occurring and annoying design bloopers from real web sites he has worked on or researched. Not just a critique of these bloopers and their sites, this book shows how to correct or avoid the blooper and gives a detailed analysis of each design problem. Hear Jeff Johnson's interview podcast on software and website usability at the University of Canterbury (25 min.) * Discusses in detail 60 of the most common and critical web design mistakes, along with the solutions, challenges, and tradeoffs associated with them. * Covers important subject areas such as: content, task-support, navigation, forms, searches, writing, link appearance, and graphic design and layout. * Organized and formatted based on the results of its own usability test performed by web designers themselves. * Features its own web site (www.web-bloopers.com)with new and emerging web design no-no's (because new bloopers are born every day) along with a much requested printable blooper checklist for web designers and developers to use.
Content bloopers -- Task-support bloopers -- Form bloopers -- Search bloopers -- Text and writing bloopers -- Link appearance bloopers -- Graphic and layout bloopers.
Includes bibliographical references (p. 310-311) and index.
Keywords: Web sites -- Design; Graphical user interfaces (Computer systems); Sites Web -- Conception; Electronic books